Mobility and Traffic-Based Analytical Study for Single and Multipath Routing Protocols in Mobile Ad Hoc Network - Yousef, Walid Shaher M.; Arshad, Muhammad Rafie Hj Mohd; Zahary, Ammar (Advanced Institutes of Convergence Information Technology, 2014)
The main purpose of this study was to assess the effectiveness of routing protocols including dynamic source routing (DSR-MP) as a multipath protocol and optimized link state routing (OLSR) and ad hoc on-demand distance vector protocol (AODV) as single path protocols over mobile ad hoc networks. This study considers the effects of different levels (low, medium, and high) for both mobility and traffic parameters on the performance of the three protocols. The main objective was to determine the most proper protocol in case of high traffic and high mobility. The simulation has been performed using the OPNET simulator for disparate scenarios of traffic and mobility. The performance has been evaluated in terms of throughput, delay, routing traffic received, and network load, which are efficiency metrics of this study. The comparative results show that OLSR outperforms AODV and DSR in the two performance metrics throughput and delay for each scenario of traffic and mobility and changes in the other two parameters. Finally, this study is considered as an essential step in evaluating and enhancing the multipath approach.